Genetic variability in the Magdalena River turtle, Podocnemis lewyana (Duméril 1852) in the Mompox Depression, Colombia (2008)
ABSTRACT: Two populations of the endangered Magdalena River turtle, Podocnemis lewyana, separated by 55 km in the Mom-pos Depression were sampled to quantify levels of genetic variation and inspect for evidence of genetic structure. Allozyme analyses resolved 22 presumptive gene loci, but only one resulted polymorphic. Genotype proportions at this locus departed from those expected under Hardy-Weinberg equilibrium, showing heterozygote deficiencies in both populations. However, allele frequencies at the locus did not differ between the two sites. The level of genetic variability documented is one of the lowest yet reported for a turtle species, and may reflect either a historical or recent bottleneck event. The lack of evidence for genetic structure suggests gene flow among the sites, at least historically, but the heterozygote deficiencies at each site also imply that inbreeding may be occurring presently within each deme.